GAMIFICATION OF ASSESSMENT: ENGAGING LEARNERS THROUGH GAME-BASED FEEDBACK - ABDURAXMONOVA, Oymonjon Alisher qizi (The Lingua Spectrum, 2025)
Gamification has emerged as a promising approach for enhancing learner engagement, motivation, and performance across diverse educational settings. This thesis investigates the role of gamified assessment – the integration of game elements such as points, badges, progress indicators, levels, and instant feedback – within formative and summative evaluation processes. The study examines how game-based feedback mechanisms influence students’ cognitive, behavioral, and emotional engagement, and whether these mechanisms contribute to deeper learning and improved academic outcomes. Drawing on a mixed-methods research design, the thesis analyzes quantitative data on learner performance and participation, as well as qualitative insights from student and instructor perceptions. The findings suggest that thoughtfully designed gamified assessment environments can foster sustained engagement, increase feedback responsiveness, and enhance learners’ sense of autonomy and competence. However, the results also highlight potential challenges, including over-reliance on extrinsic rewards and the need for pedagogically aligned gamification strategies. Overall, the research contributes to a deeper understanding of how game-based feedback can be leveraged to create more interactive, motivating, and learner-centered assessment practices in higher education.